Promotion strategy of Muhammadiyah University of Yogyakarta (UMY) in 2024-2025 in facing competition with State Universities with Legal Entity Status (PTN-BH) (BIS Humanities and Social Science, 2026)
This research examines how Universitas Muhammadiyah Yogyakarta (UMY) develops a promotional strategy to compete with State Universities with Legal Entity Status (PTN- BH) in 2024-2025. This topic comes from the recent policy that PTN-BH (Universities with Legal Entity Status) have greater advantages, including greater autonomy, substantial financial support, and a public perception that generally ranks PTN as the preferred option over Private Universities (PTS). Because of this, private universities like UMY need to devise specific strategies to promote themselves to stay competitive. This study utilizes promotion theory as a framework to analyze UMY’s management of its promotional mix. The selected methodology is a descriptive, qualitative approach that employs data collection through semi-structured interviews and documentation. The Sub-Directorate of Public Relations and Media, the Sub-Directorate of Branding and Marketing, and the Sub-Directorate of UMY Admissions are all involved in this initiative. It provides a comprehensive view of the strategy from various perspectives. The research indicates that UMY employs two distinct promotional approaches: soft selling and hard selling. In soft-selling, UMY attempts to enhance its image by highlighting its successes, showcasing innovative ideas from faculty and students, and ensuring that its social media and website content is of the highest quality. Hard selling is done more directly, such as by visiting schools and disseminating persuasive digital content across various platforms. In general, these two strategies work together to help UMY stay competitive and even improve as an excellent private university, especially as PTN-BH becomes more competitive.